Epidemiology and aetiologies of cryptococcal meningitis in Africa, 1950–2017: protocol for a systematic review. Issue 7 (30th July 2018) - Nyazika, Tinashe K; Tatuene, Joseph Kamtchum; Kenfak-Foguena, Alain; Verweij, Paul E; Meis, Jacques F; Robertson, Valerie J; Hagen, Ferry
Abstract : Introduction: Cryptococcal meningitis is a neglected disease and an AIDS-defining illness, responsible for 15% of all AIDS-related deaths globally. In 2014, the estimated number of incident cryptococcal meningitis cases was 223 100, with 73% of them occurring in Africa. Currently available data on the prevalence, incidence, aetiologies and mortality of cryptococcal meningitis across Africa are sparse and of limited quality. We propose to conduct the first systematic review to summarise the epidemiological data available on cryptococcal meningitis and its aetiological causes in Africa. Methods and analysis: We will search PubMed, MEDLINE, Excerpta Medica Database, ISI Web of Science, Africa Index Medicus, Cumulative Index to Nursing and Allied Health for studies on cryptococcal meningitis published between 1st January 1950 and 31st December 2017, involving adults and/or children residing in Africa. After study selection, full text paper acquisition and data extraction, we will use validated tools and checklists to assess the quality of reporting and risk of bias for each study. Heterogeneity across studies will be assessed using the χ 2 test on Cochrane's Q statistic and a random effect meta-analysis will be used to estimate the overall prevalence, incidence density and mortality of cryptococcal meningitis across studies with similar characteristics. This protocol is prepared and presented in accordance with the 2015 Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. Reporting of the results will be compliant with the Meta-Analysis Of Observational Studies in Epidemiology (MOOSE) guidelines. Ethics and dissemination: There is no requirement for ethical approval since we will be using data from published studies. The final report will be published in a peer-reviewed journal and further presented at conferences. This study is expected to provide useful contextual estimates needed to inform treatment policies on the African continent and assess the impact of diagnostic and prevention strategies on the burden of cryptococcal meningitis in the post antiretroviral therapy era. PROSPERO registration number: CRD42017081312.